Evaluation of galectin-3 and other biochemical parameters in chronic kidney disease patients on hemodialysis in Erbil city - M. Abdullah, Zereen; Y. Mohammadamin, Kamaran (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: Chronic kidney disease represents a leading cause of death in many countries. End-stage renal disease is the final stage of chronic kidney disease, in which the kidneys are no longer function well enough for the patient to live without renal replacement therapy. Galectin-3 is a soluble beta-galactoside-binding lectin protein involved in the fibrosis of many solid organs, including the heart and kidney. This study aimed to evaluate galectin-3 and other biochemical parameters in hemodialysis patients. Methods: The design is a cross-sectional study with a comparison group. A total of 70 chronic kidney disease patients on regular hemodialysis from Erbil Dialysis Center in Erbil City and 68 healthy subjects were enrolled. The serum levels of galectin-3 were determined by enzyme-linked immunosorbent assay method. Results: The mean level of serum galectin-3 was non-significantly higher in hemodialysis patients compared to the control group (P = 0.594). However, the serum level of galectin-3 was significantly higher in hemodialysis patients with cardiovascular disease compared to hemodialysis patients without cardiovascular disease (P = 0.0220). Serum galectin-3 level was significantly higher in hemodialysis patients aged 36-50 and 51-70 years old compared to hemodialysis patients aged 20-35 years old (P = 0.013, P = 0.026), respectively. Conclusion: Serum galectin-3 might be used as a biomarker for hemodialysis patients with cardiovascular disease.